Proof Methodologies PDF
Document Details

Uploaded by CoolWhale9420
Tags
Summary
This document provides an overview of proof methodologies, including proof by contradiction, existence proofs, and proof by cases. It also discusses examples and counter-examples. The document appears to be learning material on discrete mathematics.
Full Transcript
Week 2 Reading Material ======================= More Proof Methodologies! ------------------------- Proof by contradiction:\ \ [Method]: 1. Consider the given mathematical statement as a propositional statement p and consider that \~p is true. 2. By the end of the proof, we intend to show...
Week 2 Reading Material ======================= More Proof Methodologies! ------------------------- Proof by contradiction:\ \ [Method]: 1. Consider the given mathematical statement as a propositional statement p and consider that \~p is true. 2. By the end of the proof, we intend to show that \~p -\> F is true, where F is always false. 3. This case is only possible when \~p is false. If negation p were false then that means p is true. [Example]: Prove that √2 is Irrational [Proof]: 1. Consider that the given mathematical statement is p: "√2 is Irrational" and let us consider the negation of it \~ p: "√2 is Rational" If √2 is rational then there exists two integers a and b such that √2 = a/ b Let us assume that a and b do not have any common factors i.e, both a and b are not even. (the fraction a/ b is in the simplest form). If we square on both sides of the expression, we have 2 = a^2^/ b^2^ - 2 b^2^ = a^2^ - Here, if we consider the value of a^2^, then we can clearly see that it is of the form 2 multiplied to some integer b^2^ - a^2^ is even - Whenever, a^2^ is even, a is even. - 2 b^2^ = (2k)^2\ ^ - 2 b^2^ = 4k^2^ - b^2^ = 2k^2^ - Here, b^2^ is of the form 2 multiplied to some integer k^2^ - b^2^ is even. - b is even. Existence Proof: ---------------- 1. Constructive Existence Proof: Consider the following values for a, b, and c respectively. a = 3, b = 4, c = 5 LHS: a^2^ + b^2^ - 32 + 42 = 9 + 16 = 25 RHS: c^2^ C^2^ = 5^2^ = 25 Here, we can clearly see that LHS = RHS Therefore, we can say that there exists values of a, b, and c such that the statement a^2^ + b^2^ = c^2^ is true. [Note]: We can also prove this mathematical statement using any of the Pythagorean Triples like (a, b, c) = (6, 8, 10); (5, 12, 13); etc... 2. Non-constructive Existence Proof: We try to prove the predicate P(x) without providing a specific example or algorithm for it. We try to show that an instance exists for proving the statement indirectly. [Example]: There exist irrational numbers x, y such that x^y^ is rational. [Proof]: Assume that x = √2 and y = √2 x^y^ = (√2) √2 Here, there are two possibilities i.e., this value could be rational/ irrational. If (√2) √2 is a rational number, then the proof completes here. [Case 2]:\ \ If (√2) √2 is Irrational, Then we will update the values such that x = (√2) √2 and y = √2 Let us evaluate the value of x^y^ now. - x^y^ = (√2^√2^) ^√2^ = √2^√2.√2^ = (√2)^2^ = 2. - Here, 2 is rational Proof By Cases: --------------- It a proof methodology used to demonstrate a statement/ predicate is true by splitting the problem into parts that are considered/ evaluated separately which are called as cases. Method: ------- [Step 1]: Show that there are a set of cases that are mutually exhaustive.\ \ [Step 2]: Prove that the statement is true in each of the provided cases. [Example]: For any integer k, the result of 3k^2^ + k is even. [Step 1]: Consider the possible cases. Here, the mathematical statement deals with the notion of the result being an even number. So, we can think of the cases wherein k is an even number and the case wherein k is an odd number. - Case 1: k is even. - Case 2: k is odd. [Step 2]: Proving the statement for the considered cases. [Case 1]: If k is even - k can be expressed as k = 2p - 3k^2^ + k = 3 (2p)^2^ + (2p) = 3 (4p^2^) + 2p = 12p^2^ + 2p - Here, 12 p^2^ + 2p can be expressed as 2 (6p^2^ + p) this is of the form of 2 multiplied to some integer 6p^2^ + p - 3k^2^ + k is in the form of an even number. [Case 2]: If k is odd - K can be expressed as k = 2p + 1 - 3k^2^ + k = 3 (2p + 1)^2^ + (2p + 1) = 3 (4p^2^ + 4p + 1) + 2p + 1\ = 12p^2^ + 12p + 3 + 2p + 1 = 12p^2^ + 14p + 4 = 2 (6p^2^ + 7p + 2) This is of the form of 2 multiplied to some integer 6p^2^ + 7p + 2 - 3k^2^ + k is in the form of an even number. Counter Example: ---------------- To show that a statement of the form of a universally quantified predicate is false, we need only one example/ instance and it is called as a counter example for the predicate/ statement. [Example]: Consider the following mathematical statement: "All prime numbers are odd." Here, if we consider the prime number to be 2, then this serves as a counter example to the above statement as 2 is an even prime number. Fallacy: -------- An instance of improper reasoning leading to an unexpected result that is false is called as a fallacy. Fallacies are usually encountered due to incorrect application of rules of logic. [Example]: Consider the following arguments: p -\> q: "If you do every problem in this book, then you will learn discrete mathematics." q: "You learned discrete mathematics." ∴ p: "you did every problem in this book."\ \ How can we check the consistency/ validity of an argument? (alternative method) We can express the set of arguments and conclusions in the form of a compound proposition ((p -\> q) ∧ q) -\> p If the arguments and conclusion are valid, then the truth table for the above expression must be a tautology. **p** **q** **(((p → q) ∧ q) → p)** ------- ------- ------------------------- F F **T** F T **F** T F **T** T T **T** Here, we can clearly see that the truth values of above compound expression is not a tautology. Therefore, the above argument and conclusion is a fallacy. Mathematical Induction (Weak Induction): ---------------------------------------- Mathematical Induction is a technique of proving a statement, theorem or formula which is thought to be true, for each and every natural number n. By generalizing this in form of a principle which we would use to prove any mathematical statement is 'Principle of Mathematical Induction'. [Method]: **Step 1: ** Check whether the given statement is true for n = 1 (or) the base case given. **Step 2: **Assume that given statement P(n) is also true for n = k, where k is any positive integer. **Step 3: ** Prove that the result is true for P(k+1) for any positive integer k. If the above-mentioned conditions are satisfied, then it can be concluded that P(n) is true for all n natural numbers from the base case. [Example]: For any positive integer number n, prove that n^3^ + 2n is always divisible by 3 [Proof]: Let P(n): n3 + 2n is divisible by 3 be the given statement. [Step 1]: Basic Step Firstly we prove that P(1) is true. Let n = 1 in n^3^ + 2n = 1^3^ + 2(1) = 3 As 3 is divisible by 3. Hence, P(1) is true. [Step 2]: Assumption Step Let us assume that P(k) is true Then, k^3^ + 2k is divisible by 3 Thus, we can write it as k^3^ + 2k = 3n (where n is any positive integer)....(i) [Step 3]: Induction Steps Now we have to prove that algebraic expression (k + 1)^3^ + 2(k + 1) is divisible by 3 = (k + 1)^3^ + 2(k + 1) = k^3^ + 3k^2^ + 5k + 3 = (k^3^ + 2 k) + (3k^2^ + 3k + 3) from eq(i) = 3n + 3(k^2^ + k + 1) = 3(n + k^2^ + k + 1) As it is a multiple of 3 we can say that it is divisible by 3. Thus, P(k+1) is true i.e. (k + 1)^3^ + 2(k + 1) is be divisible by 3. Now by the Principle of Mathematical Induction, we can say that, P(n): n3 + 2n is divisible by 3 is true. Strong Induction: ----------------- Proof by strong induction is a mathematical technique for proving universal generalizations. It differs from ordinary mathematical induction (also known as weak mathematical induction) with respect to the inductive step. In a weak mathematical induction, the inductive step involves showing that if some element n has a property, then the successor element n + 1 must also have that property. In a strong mathematical induction, the inductive step involves showing that if all elements up to and including n have some property, then n + 1 has that property as well. [Method]: **Step 1: Basis Step:** We prove that P(1) is true or the base case is true. **Step 2:** **Induction Hypothesis:** P(1) \^ P(2) \^... \^ P(k) is true **Step 3:** **Inductive Step:** If P(1) \^ P(2) \^... \^ P(k) is true for arbitrary k, We show that P(k + 1) is true. Example: For any positive integer n, greater than 1, n can be written as the product of one or more prime numbers. [Proof:] By strong induction, - Here, the domain is the set of positive integers greater than 1 - Integers greater than or equal to 2. 1. [Basis Step:] We show that P(2) is true Since 2 is a prime number, it can be written as a product of itself. Therefore, P(2) is true. 2. [Inductive Hypothesis:] Assume that P(2) \^... P(k) is true. 3. [Inductive step:] Consider the number (k+1) Here, we can intuitively think of two possibilities i.e, k+1 being a prime number or a composite number. Case 1: If k + 1 is prime, - k + 1 can be written as the product of itself. Therefore, k +1 is true for this case. Case 2: If k + 1 is composite, - k + 1 can be written as the product of two numbers - (k + 1) = a x b; such that 1 \< a \ common difference. (difference of any two consecutive terms in the series) - n^th^ term of an Arithmetic progression is given by a~n~ = a + (n -- 1) d - The sum of n terms of an AP is calculated by S~n~ = n/2 \[2a + (n -- 1) d\] (or) n/2\[ a + l\] Where, n -\> number of terms a -\> first term d -\> common difference. S~n~ -\> Sum of n terms l -\> Last term of the sequence. Harmonic Progression: --------------------- A sequence of the form 1/a, 1/a + d, 1/ a + 2d,.... Is called as a Harmonic Progression. [Note:] If h~1~, h~2~,..., h~n~ are the terms of a harmonic progression, then 1/h~1~, 1/h~2~,.... Form the terms of an Arithmetic Progression. Geometric Progression: ---------------------- A sequence of the form a, ar, ar^2^, ar^3^,... ar^n^ is called as a geometric progression. Where, a -\> first term. r = a~2~/ a~1~-\> common ratio (ratio of two consecutive terms in the sequence) The n^th^ term of a GP is given by a~n~ = ar^n\ --\ 1^ The sum of n terms of a GP is given by S~n~ = a(1 -- r^n^)/(1 -- r) (if 1 \> r) S~n~ = a (r^n^ - 1)/(r - 1) (if 1 \< r) The sum of infinite terms of a GP is given by a/1 - r